2016
DOI: 10.1167/iovs.15-17769
|View full text |Cite
|
Sign up to set email alerts
|

Time-Lapse Retinal Ganglion Cell Dendritic Field Degeneration Imaged in Organotypic Retinal Explant Culture

Abstract: PurposeTo develop an ex vivo organotypic retinal explant culture system suitable for multiple time-point imaging of retinal ganglion cell (RGC) dendritic arbors over a period of 1 week, and capable of detecting dendrite neuroprotection conferred by experimental treatments.MethodsThy1-YFP mouse retinas were explanted and maintained in organotypic culture. Retinal ganglion cell dendritic arbors were imaged repeatedly using confocal laser scanning microscopy. Maximal projection z-stacks were traced by two masked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 46 publications
0
25
0
Order By: Relevance
“…Our new explant model utilizes methods by which fundamental changes in axons can be quantitatively measured, using laser scanning images of the ONH and retrobulbar optic nerve, the site of initial glaucoma damage. Previous models, including dissociated RGC (Welsbie et al, 2013), retinal explant cultures (Bull et al, 2011; Johnson et al, 2016) and eye cup models (Ishikawa et al, 2014), have been reported in which RGC survive for 1-2 weeks without a blood supply, despite transected axons, allowing repeated measures of RGCs over time. These each have advantages, but none preserves the actual tissue relationships of RGC axons in the ONH, and none permits manipulation of IOP in the intact globe to determine its effect in real time on the axons and astrocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our new explant model utilizes methods by which fundamental changes in axons can be quantitatively measured, using laser scanning images of the ONH and retrobulbar optic nerve, the site of initial glaucoma damage. Previous models, including dissociated RGC (Welsbie et al, 2013), retinal explant cultures (Bull et al, 2011; Johnson et al, 2016) and eye cup models (Ishikawa et al, 2014), have been reported in which RGC survive for 1-2 weeks without a blood supply, despite transected axons, allowing repeated measures of RGCs over time. These each have advantages, but none preserves the actual tissue relationships of RGC axons in the ONH, and none permits manipulation of IOP in the intact globe to determine its effect in real time on the axons and astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The first expresses yellow fluorescent protein (YFP) in a small number of RGCs. Previously, we and others (Danaf and Huberman, 2015; Johnson et al, 2016; Kalesnykas et al, 2012; Leung et al, 2011) have studied changes in RGC bodies and dendrites of the RGC-YFP strain with chronic IOP elevation. Some investigations were performed by cross-sectional study in histological preparations, while others observed sequential events in these cells by ophthalmoscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, Thy1-YFP mice have recently been used to develop an organotypic culture model where RGCs are fluorescently labeled. This line provides a useful tool for time-lapse imaging of the outgrowing neurites (Johnson et al 2016). Retinal explants can be harvested from embryonic, postnatal or adult eyes, whether or not primed by optic nerve injury.…”
Section: Ex Vivo Tissue Explant Studies In Rodentsmentioning
confidence: 99%
“…While retinal explants from adult animals of a variety of species including mouse, rat and zebrafish have been utilized for different cell biological approaches 1720 , live-cell imaging experiments using retinal explants have been restricted to brief periods of time and have not been executed continuously over several hours. 21, 22 Here, we describe a detailed protocol to culture light-damaged adult zebrafish retinas to perform live-cell imaging experiments monitoring INM using multi-photon microscopy 6 . Live-cell imaging approaches are advantageous over immunohistochemical methods when investigating the mechanisms controlling INM, as the dynamics of INM e.g.…”
Section: Introductionmentioning
confidence: 99%